Impact of methotrexate dose on efficacy of adalimumab in Japanese patients with rheumatoid arthritis: Results from registered data analyses. Issue 1 (2nd January 2017) - Nakashima, Yasuharu; Miyahara, Hisaaki; Kondo, Masakazu; Fukuda, Takaaki; Harada, Hiroshi; Haraguchi, Akihisa; Inoue, Yasushi; Ishinishi, Takashi; Maekawa, Masayuki; Maeyama, Akira; Nakashima, Munetoshi; Shono, Eisuke; et al.
Abstract: Objective : Upper limit of methotrexate (MTX) for patients with rheumatoid arthritis (RA) was recently increased from 8 to 16 mg/week in Japan. We therefore examined the effect of concomitant MTX dose on the efficacy of adalimumab (ADA) in clinical practice. Method : Sixty-one consecutive RA patients treated with ADA were followed for minimum 52 weeks and retrospectively compared by MTX dose; patients receiving concomitant MTX of 10 mg/week or more (MTX ≥10 mg group) and <10 mg/week (MTX <10 mg group). Disease activity and remission were evaluated by the disease activity score 28 (DAS28) criteria. Results : The MTX ≥10 mg group consistently showed better improvement in DAS28 and resulted in more patients (52.8%) with DAS28-remission compared with the MTX <10 mg group (26.1%). Multivariate analysis showed that MTX ≥10 mg had a significant effect on DAS28 remission with odds ratio of 5.12. ADA retention rate was 72.2% in MTX ≥10 mg group compared with 52.0% in MTX <10 mg group. Discontinuation of ADA due to adverse events were comparable in the MTX ≥10 mg and MTX <10 mg groups (11.1% vs. 12.0%). Conclusions : These findings support the critical role of concomitant MTX in the efficacy of ADA, and recommend use of MTX ≥10 mg in Japanese RA patients.